Development of a Reporter System Monitoring Regulated Intramembrane Proteolysis of the Transmembrane bZIP Transcription Factor ATF6α - Kim, Jin-Ik (Mol Cells, 2019)
When endoplasmic reticulum (ER) functions are perturbed, the ER induces several signaling pathways called unfolded protein response to reestablish ER homeostasis through three ER transmembrane proteins: inositol-requiring enzyme 1 (IRE1), PKR-like ER kinase (PERK), and activating transcription factor 6 (ATF6). Although it is important to measure the activity of ATF6 that can indicate the status of the ER, no specific cell-based reporter assay is currently available. Here, we report a new cell-based method for monitoring ER stress based on the cleavage of ATF6α by sequential actions of proteases at the Golgi apparatus during ER stress. A new expressing vector was constructed by using fusion gene of GAL4 DNA binding domain (GAL4DBD) and activation domain derived from herpes simplex virus VP16 protein (VP16AD) followed by a human ATF6α N-terminal deletion variant. During ER stress, the GAL4DBD-VP16AD(GV)-hATF6α deletion variant was cleaved to liberate active transcription activator encompassing GV-hATF6α fragment which could translocate into the nucleus. The translocated GV-hATF6α fragment strongly induced the expression of firefly luciferase in HeLa Luciferase Reporter cell line containing a stably integrated 5X GAL4 site-luciferase gene. The established double stable reporter cell line HLR-GV-hATF6α(333) represents an innovative tool to investigate regulated intramembrane proteolysis of ATF6α. It can substitute active pATF6(N) binding motif-based reporter cell lines.